KONSTRUKSI HUKUM TINDAKAN ADMINISTRASI KEIMIGRASIAN: STUDI KASUS IMMIGRATOIR, ASYLUM SEEKER DAN REFUGEE - Firdaus, Muhammad Yani (WICARANA, 2025)
Indonesia is a country strategically positioned at the crossroads of the world, a fact that has significant implications for global human movement with diverse visions and missions. The dynamics of such global mobility inevitably influence the geopolitical and geostrategic policies of the Government of the Republic of Indonesia, especially given its unique geographical conditions and location at a global intersection. This reality underlies the role of the Ministry of Law and Human Rights of the Republic of Indonesia, particularly the Directorate General of Immigration, which serves as the gatekeeper of national sovereignty. This role is encapsulated in the motto Bhumi Pura Wira Wibawa, meaning the Authoritative Gatekeeper of the State. With this guiding principle, the Directorate General of Immigration bears responsibility not only for delivering quality immigration services but also for enforcing the law, safeguarding state security, and supporting the development of community welfare. One of the key manifestations of this responsibility lies in carrying out measurable and systematic Immigration Administrative Actions. These actions require strong coordination across institutions and active involvement of various elements of society, ensuring that immigration management is both comprehensive and sustainable.